AI in Administrative Dispute Resolution: Exploring Opportunities and Risks - Wibowo, Esa Maulana; Nte, Ngaboawaji Daniel; Kusuma, Bagus Hendradi (Universitas Negeri Semarang, 2024)
The integration of Artificial Intelligence (AI) into the resolution of administrative disputes presents both significant opportunities and potential risks within the legal framework. As administrative courts globally face growing caseloads and demands for faster, more efficient decision-making, AI offers a promising solution for enhancing the speed, accuracy, and consistency of legal processes. This research explores the potential applications of AI in Indonesia's administrative justice system, focusing on its role in case management, decision support, and predictive analytics. The findings highlight several key opportunities, including AI’s potential to streamline case processing, reduce human error, and improve access to justice by automating routine tasks. Additionally, AI can help predict legal outcomes based on data-driven insights, offering both practitioners and courts valuable tools to enhance decision-making. However, the study also identifies significant risks, such as the potential for bias in algorithmic decision-making, lack of transparency, and concerns over the loss of human oversight in critical legal decisions. These risks may undermine the fairness and accountability of administrative dispute resolution. The novelty of this research lies in its focus on the intersection of AI and administrative law, offering a fresh perspective on how emerging technologies can be harnessed to improve judicial efficiency while addressing the inherent challenges. The urgency of this exploration is underscored by the increasing demand for reforms in administrative justice systems. This study contributes valuable insights for policymakers and legal professionals on how to balance innovation with safeguards to ensure AI’s responsible and equitable use in administrative dispute resolution.